Variations on the Theme of Remembering: A National Survey of How Canadians Use the Past - Friesen, Gerald; Muise, Del; Northrup, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
AbstractThis paper in collective remembering is based on a telephone survey of 3,419 adult residents of Canada. The questionnaire contains over 70 questions. The interviews average over 20 minutes in length. Part of the Canadians and Their Pasts project, the survey seeks to assess how Canadians use the past in daily life. How many engage in activities related to the past, such as reading books, viewing photos, or visiting museums and historic sites? How do they evaluate different sources of information about the past? What types of past — family, province, nation, ethnic group — are most important to them? The paper suggests that the construction and reconstruction of autobiographical memory is a fundamental aspect of one’s uses of the past. It also proposes that wider collective pasts are particularly important among members of minority and alternative groups. And that the past of the nation-state figures more prominently in these citizens’ reflections than Roy Rosenzweig and David Thelen observed in their similar study, The Presence of the Past: Popular Uses of History in American Life (1998).